STRATEGIC BUYER SATISFACTION: A PROBLEM OF COMMUNICATION, COMMITMENT AND CONFLICT RESOLVE - Gatut L Budiono (Jurnal Manajemen, 2016)
This study had been referred to the results of research of Selnes (1996), Sumarto et al (2012), about antecendents and consequences of trust and satisfaction in buyer-seller relationships. Primary data and correlational method were incorporated. Commitment of the seller strongly associated with customer satisfaction, the better the commitment of the seller was increasing customer satisfaction. Communication seller strongly associated with satisfaction of the buyer, the better sellers communicate has increased customer satisfaction. Strong problem solving related to customer satisfaction, the better the settlement of the problem by sellers has increased customer satisfaction.